Effect of segregation on deformation behaviour of nanoscale CoCrCuFeNi high-entropy alloy - Kazakov, Arseny M. (2023)
A molecular dynamics (MD) simulation method is used to investigate the effect of grain boundary (GB) segregation on the deformation behavior of bicrystals of equiatomic nanoscale CoCrCuFeNi high-entropy alloy (HEA). The deformation mechanisms during shear and tensile deformation at 300 K and 100 K are analyzed. It is revealed that upon tensile deformation, the stacking fault formation, and twinning are the main deformation mechanisms, while for the shear deformation, the main contribution to the plastic flow is realized through the GB migration. The presence of the segregation at GBs leads to the stabilization of GBs, while during the shear deformation of the nanoscale CoCrCuFeNi HEA without the segregation at GBs, GBs are subject to migration. It is found that the GB segregation can differently influence the plasticity of the nanoscale CoCrCuFeNi HEA, depending on the elemental composition of the segregation layer. In the case of copper and nickel segregations, an increase in the segregation layer size enhances the plasticity of the nanoscale CoCrCuFeNi HEA. However, an increase in the thickness of chromium segregations deteriorates the plasticity while enhancing maximum shear stress. The results obtained in this study shed light on the development of HEAs with enhanced mechanical properties via GB engineering.